2011
DOI: 10.1093/nar/gkr1224
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus-1 Tat activates NF-κB via physical interaction with IκB-α and p65

Abstract: Nuclear factor (NF)-κB is a master regulator of pro-inflammatory genes and is upregulated in human immunodeficiency virus 1 (HIV-1) infection. Mechanisms underlying the NF-κB deregulation by HIV-1 are relevant for immune dysfunction in AIDS. We report that in single round HIV-1 infection, or single-pulse PMA stimulation, the HIV-1 Tat transactivator activated NF-κB by hijacking the inhibitor IκB-α and by preventing the repressor binding to the NF-κB complex. Moreover, Tat associated with the p65 subunit of NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 75 publications
6
125
0
2
Order By: Relevance
“…This broad antitranscriptional activity of INK128 is consistent with inhibition of mTORC2, whose activity is important for phosphorylation of PKC isoforms (including isoforms α and θ) (9,(20)(21)(22), and, in turn, induction of NF-κB (23,24). By interfering with NF-κB induction, INK128 may prevent recruitment of the host transcription factor P-TEFb to the HIV LTR, thereby decreasing virus transcription (23,43,44). In infectivity assays using primary PBLs, INK128 inhibited both R5 and X4 HIV, laboratory-adapted and primary isolates, with EC 50 values < 50 nM.…”
Section: Discussionmentioning
confidence: 65%
“…This broad antitranscriptional activity of INK128 is consistent with inhibition of mTORC2, whose activity is important for phosphorylation of PKC isoforms (including isoforms α and θ) (9,(20)(21)(22), and, in turn, induction of NF-κB (23,24). By interfering with NF-κB induction, INK128 may prevent recruitment of the host transcription factor P-TEFb to the HIV LTR, thereby decreasing virus transcription (23,43,44). In infectivity assays using primary PBLs, INK128 inhibited both R5 and X4 HIV, laboratory-adapted and primary isolates, with EC 50 values < 50 nM.…”
Section: Discussionmentioning
confidence: 65%
“…First, in glioblastoma and prostate cancer, miR-222 is activated by NFkB and AP-1, 11 two very well-characterized factors that regulate HIV-1 transcription. Second, a recent paper reported that Tat associates with the p65 subunit of NFkB and increases both the DNA-binding affinity and the transcriptional activity of p65 12 . Thus, we transduced HeLa cells with a Flag-tagged Tat-expressing construct and measured the levels of miR-222 by qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Cell transfection with the pNF-jB-Luc (pjBLuc) reporter plasmid was carried out as previously described (Fiume et al, 2012;Vitagliano et al, 2011). U251 cells were cultured in a DMEM/Ham's F12 (1:1 ratio) supplemented with 10% heat-inactivated fetal calf serum, 2 mM L-glutamine, 1 mM sodium pyruvate and 1 mM non-essential amino acids, and were transfected with DNA by using FuGENE HD (Roche Diagnostic GmbH, Mannheim, Germany), according to the manufacturer's protocol.…”
Section: Cells Transfection Treatments and Luciferase Assaymentioning
confidence: 99%